2015
DOI: 10.1515/chem-2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

Use of ATR-FTIR spectroscopy to detect the changes in extra virgin olive oil by adulteration with soybean oil and high temperature heat treatment

Abstract: Abstract:The structural changes induced in extra virgin olive oil (EVOO) by adulteration with soybean oil (SBO) and heat treatment at 185°C for 4 and 8 h were investigated using Attenuated Total Reflectance -Fourier Transform Infrared (ATR-FTIR) spectroscopy. Our results revealed that the band around 3006 cm -1 recorded shifts versus the percentage of adulterant. The changes in the absorbance at 3006 cm -1 (A3006) and in the ratio of the maximum heights of the bands at 3006 and 2925 cm −1 (A3006/A2925) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 30 publications
6
69
0
3
Order By: Relevance
“…The peak at 3,006 cm −1 (cis-olefin CH stretching peak) has been reported to be useful in distinguishing different types of oils based on their percentage of unsaturation as well as detecting adulteration in oil samples (Poiana et al, 2015). It was found that the peak shifted from 3,007 to 3,005 cm −1 as olive oil was added to canola oil ( Figure 17).…”
Section: Ftir Spectramentioning
confidence: 97%
See 1 more Smart Citation
“…The peak at 3,006 cm −1 (cis-olefin CH stretching peak) has been reported to be useful in distinguishing different types of oils based on their percentage of unsaturation as well as detecting adulteration in oil samples (Poiana et al, 2015). It was found that the peak shifted from 3,007 to 3,005 cm −1 as olive oil was added to canola oil ( Figure 17).…”
Section: Ftir Spectramentioning
confidence: 97%
“…The ratio between peaks at 3,006 and 2,925 cm −1 has been reported to be important in detecting adulteration in olive oil (Poiana et al, 2015). Therefore, the ratio was plotted against the percentages of olive and sesame oils in the blends.…”
Section: Ftir Spectramentioning
confidence: 99%
“…Moreover, the peaks in the bands at 3000-2800 cm −1 and 1800-1600 cm −1 can be attributed to C-H stretching and carbonyl groups. While thermal treatment at 120 • C does not affect zeolite stability, it results in oil degradation (a reduction of C=C stretching and the secondary products), creating a thin adsorbing layer of zeolite grains adhered to the metallized glass substrate [46]. Adsorption characteristics of the layer were investigated by gravimetric analysis of H 2 O.…”
Section: Sensor Manufacturing and Characterizationmentioning
confidence: 99%
“…Additionally, spectra of liquids modified with surfactant Span ® 20 are shown. The infrared spectra of investigated liquids ( Figure 5) contain fundamental and characteristic bands whose frequencies and intensities can determine the relevant functional groups in the investigated liquids [82][83][84].…”
Section: Attenuated Total Reflection-fourier Transform Infrared (Atr-mentioning
confidence: 99%
“…The infrared spectra of investigated liquids ( Figure 5) contain fundamental and characteristic bands whose frequencies and intensities can determine the relevant functional groups in the investigated liquids [82][83][84]. Two of the studied liquids were esters (synthetic and natural esters), and absorption bands attributed to vibrations of esters were present at their spectra.…”
Section: Appl Sci 2018 8 2538 9 Of 22mentioning
confidence: 99%